Optical limiting behavior, nonlinear optical studies, geometrical descriptors, chemical properties data, topology analysis on tetraethylammonium L-tartarate dihydrate crystals. Issue 1 (13th April 2022) - Vivek, P.; Rekha, M.; Suvitha, A.; Kumar, G. Saravana; Jauhar, Ro. Mu.; Mahesh, M.; Kowsalya, M.; Steephen, Ananth
Abstract: The slow cooling technique was utilized to grow organic single crystals of tetraethylammonium L-tartarate dehydrate (EAT) with dimensions 20 × 4 × 4 mm 3 . The meta stable zone width was obtained via solubility curve. Structural confirmation was achieved using X-ray diffraction. EAT possesses noncentro symmetric P21 space group within the monoclinic crystal structure. Optical transmittance in the visible region reveals a strong transparency with lower cutoff wavelength of 261 nm. EAT crystal's refractive index is 1.611. The EAT compound's thermal stability was found to be 115 °C, measured by TG-DTA experiments. EAT's specific heat capacity is be 3.670  g −1 K −1 . The laser damage threshold of grown EAT crystal surface was measured at 0.3611 GW/cm 2 . Vicker's microhardness, Kurtz-Perry Powder Method evaluated the mechanical power, particle size based second harmonic generation efficiency (SHG) which identified phase matching in EAT. The SHG maker Fringes technique investigated the SHG of EAT. Optical limiting analysis showed transmitted output power rises linearly till 2.736 mW mm −2 of irradiance. Abstract : UF0001